KADAR DEBU TOTAL AMBIEN DI TERMINAL PETI KEMAS PT. PELINDO III BANJARMASIN DAN DAMPAKNYATERHADAP KESEHATAN MASYARAKAT - Fitriani Fitriani; Emmy Sri Mahreda; Idiannor Mahyudin; Danang Biyatmoko (Universitas Lambung Mangkurat, 2016)
The purpose of this research are: 1) to analyze how much ambient of dust content in the vicinity of the Container Terminal PT. Pelindo III Banjarmasin Banjarmasin, 2) To analyze the levels of air pollution caused by ambient dust in the vicinity of the Container Terminal PT. Pelindo III Banjarmasin Banjarmasin, and 3) To analyze the relationship between the amount of dust in the health status of workers and surrounding communities around Container Terminal PT. Pelindo III Banjarmasin Banjarmasin. The average quality of dust ambient at Container Terminal PT. Pelindo III Banjarmasin Banjarmasin has exceeded the threshold required under Regulation 41 of 1999, which amounted to 974.1 mg/Nm3 on the location of the terminal entrance and 941.2 in stacking terminal locations, while in residential areas is still far below the quality standards required namely 51,5 μg/Nm3. There is correlation between the quality of dust ambient at Container Terminal PT. Pelindo III Banjarmasin Banjarmasin with public health, with r = -0.40. This result shows strong correlation between levels of dust ambient with health workers and communities around the Container Terminal PT. Pelindo III Banjarmasin Banjarmasin. Meanwhile, in the nearby residential areas indicates that there is no significant correlation between level of dust ambient to public health, where r = 0.40. This indicates that the level of dust content in the Container Terminal PT. Pelindo III Banjarmasin Banjarmasin not too closely related to public health.